2006
DOI: 10.1055/s-2006-927232
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Wall-Sign in Pulmonary Echinococcosis (New Application)

Abstract: We conclude that a double layered border in univesicular and double layered internal septum in multivesicular pulmonary echinococcal cysts is a reliable indicator of pulmonary echinococcosis, with a specificity of 66 % and 100 %, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
12
0
3
Order By: Relevance
“…Even a thin layer (1e2 cm) of air can seriously reduce the visualization of solid lesions, regardless of their size. In certain cases, US imaging can also reveal deeper-seated pulmonary lesions, e.g., when the surrounding parenchyma is consolidated, i.e., atelectatic, or when the lesion is surrounded by a pleural effusion, which acts as an acoustic window [16].…”
Section: Pulmonary Diseasesmentioning
confidence: 99%
“…Even a thin layer (1e2 cm) of air can seriously reduce the visualization of solid lesions, regardless of their size. In certain cases, US imaging can also reveal deeper-seated pulmonary lesions, e.g., when the surrounding parenchyma is consolidated, i.e., atelectatic, or when the lesion is surrounded by a pleural effusion, which acts as an acoustic window [16].…”
Section: Pulmonary Diseasesmentioning
confidence: 99%
“…The specificity was 66% and 100% in the univesicular and multivesicular cysts, respectively. 19 Plain chest x-ray detected only 57 of 79 pulmonary cysts detected by CT in the study by Erdem et al 20 Magnetic resonance imaging can also be used in the diagnosis of pulmonary hydatid disease. 21,22 Laboratory testing should be used either in highly suspicious cases or for the postoperative follow-up of pulmonary hydatid cyst disease.…”
Section: Discussionmentioning
confidence: 99%
“…On their own, these images were not pathognomonic of pulmonary echinococcosis. Ultrasonography has recently been found to be particularly useful in the diagnosis of pulmonary echinococcal cysts, revealing a double-layered cystic wall that is very indicative of such cysts, with specificities of 66% for the unilocular cysts and 100% for the multivasicular (El Fortia et al, 2006). Although eosinophilia (with .500 eosinophils/ml) may help confirm a suspected case of pulmonary echinococcosis (Jerray et al, 1992), it is only observed in 20%-30% of echinococcosis cases, becoming more common after cyst rupture.…”
Section: Discussionmentioning
confidence: 99%